(untitled) - Thomas, Hugh (London, 1981)
Following the paths of Herodotus, Raleigh and H.G. Wells, this updated edition surveys the story of humankind, from the dawn of man to the hopes that will carry the world through the last years of the 20th century. The book won the National Book Award for History in 1980. Hugh Thomas also won the Somerset Maugham Prize in 1962 for his book, "The Spanish Civil War".
Keywords: Civilization; History